Ecological and molecular studies on emerging schistosomiasis mansoni in Dhofar Governorate, Sultanate of Oman - Moné, Hélène; Mouahid, Gabriel; Shaban, Mahmoud A.; Jabri, Ali A. Al; Boissier, Jérôme; Ruppel, Andreas; Idris, Mohamed A. (Tropical medicine & international health, 2003)
The recent detection of some cases of autochtonous schistosomiasis mansoni in Dhofar, Oman, prompted a search for the transmission sites. The five field surveys we conducted from November 2000 to February 2002 provided ecological data on schistosomiasis in Dhofar. Twenty-eight water bodies situated within 8-160 km from Salalah, the largest city of Dhofar and at altitudes of up to 900 m, were surveyed for freshwater snails. Biomphalaria arabica was found in 15 of them. Three sites (Tibraq, Siginitti and Arazat) had Schistosoma infected snails, the first snails shedding cercariae of this parasite ever collected in Oman. The parasite from Dhofar was analysed by Random Amplified Polymorphic DNA comparisons using 11 primers and 167 polymorphic fragments and had 87-88% similarity with Schistosoma mansoni from Guadeloupe, but only 37-38% similarity with S. rodhaini from Burundi. Thus, it is a strain of S. mansoni. During the November 2000 survey, the prosobranch snail Melanoides tuberculata was associated with B. arabica in 10 of the 13 B. arabica sites. Cercariae from other species of Digenea emerged from five of the B. arabica sites, including the three named above. This paper presents the first finding of S. mansoni in the Dhofar Governorate and represents an initial study of the biology of S. mansoni transmission. This parasite and its cycle need further biological and molecular characterization, and the clarification of its epidemiological status in Dhofar Governorate is an urgent task.
First published: 10 March 2003
Gesehen am 12.04.2021